2013
DOI: 10.1590/s1413-81232013000400012
|View full text |Cite
|
Sign up to set email alerts
|

Formação de coordenadores pedagógicos em alimentação escolar: um relato de experiência

Abstract: This article describes the experience of in-service training for pedagogical coordinators of the Brazilian School Nutrition Program (PNAE) developed by the Cooperation Center for Student Food and Nutrition of the Federal University of Bahia (CECANE-UFBA). Participant observation and analysis of data documented in films, group discussion summaries, procedural and final evaluations and field diaries are used. The formative experiences were in 2011, in two municipalities in Bahia and Sergipe states, involving 118… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
18

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 3 publications
0
5
1
18
Order By: Relevance
“…9,11 No presente estudo, a utilização de oficina de arte culinária e da horta escolar como estratégia de EAN representa práticas que oportunizam, além do contato sensorial com os alimentos, a criatividade e vivência de valores, sentimentos e experiências sobre alimentação, saúde e cultura. 28 A interação entre o cozinhar e o cultivar, considera o alimento uma referência nessas ações, valoriza o consumo de alimentos locais e regionais, 29,30 incorpora o lúdico ao processo de aprendizagem e favorece a reflexão, a iniciativa, e a associação da brincadeira com a realidade. 1 Ao serem questionados sobre a periodicidade das ações de EAN nas escolas e creches, predominou a frequência semestral (n=128, 38,8%) e (n=105, 40,1%), respectivamente.…”
Section: Tabela 1 Caracterização Do Exercício Profissional Do Nutricunclassified
See 1 more Smart Citation
“…9,11 No presente estudo, a utilização de oficina de arte culinária e da horta escolar como estratégia de EAN representa práticas que oportunizam, além do contato sensorial com os alimentos, a criatividade e vivência de valores, sentimentos e experiências sobre alimentação, saúde e cultura. 28 A interação entre o cozinhar e o cultivar, considera o alimento uma referência nessas ações, valoriza o consumo de alimentos locais e regionais, 29,30 incorpora o lúdico ao processo de aprendizagem e favorece a reflexão, a iniciativa, e a associação da brincadeira com a realidade. 1 Ao serem questionados sobre a periodicidade das ações de EAN nas escolas e creches, predominou a frequência semestral (n=128, 38,8%) e (n=105, 40,1%), respectivamente.…”
Section: Tabela 1 Caracterização Do Exercício Profissional Do Nutricunclassified
“…Santos et al, 30 ao desenvolverem uma proposta formativa para coordenadores pedagógicos sobre alimentação e nutrição no ambiente escolar, identificaram que as práticas educativas, ainda que dinâmicas e interativas, necessitam de aperfeiçoamento. A motivação e a sensibilização desses atores sociais podem ser fragilizadas no cotidiano de trabalho, por falta de uma ação permanente e abrangente.…”
Section: Uma Resistência Em Algumas Escolas Em Relação a Querer Abrirunclassified
“…Conner et al 12 and Santos et al 26 agree that skilled workers are critical for the acquisition of school foods.…”
Section: Discussionmentioning
confidence: 99%
“…16 Two public power initiatives promoting the development of school gardens in Brazil are worth of mention: the Health at School Program (Programa Saúde na Escola), which promotes pedagogical school gardens as a strategy for knowledge building and skills development among school children, enabling them to produce, discover, select and consume foods in an adequate, healthy, safe and playful manner; 19 and the joint initiative of the Food and Agriculture Organization (FAO) with the Brazilian Education Development Fund (FNDE), called "Educating with School Gardens (Educando com a Horta Escolar), which provides educational activities in food and nutrition within schools through school-based gardens and practical classes in a range of different subjects involving both teachers and students, and fosters an integrated discussion on food, nutrition, the environment and school curriculum. 20 Some studies have reported experiences and topics within schools involving the gardens implemented under the program, including agroecology, 21 science teaching, 22 sustainable practices; 23 environment education, 24 among others. Studies have also reported that as children's exposure to vegetables increased, their vegetable intake increased, and this event may have positive impacts on attitudes, preferences and eating behavior.…”
Section: 14mentioning
confidence: 99%